2019
DOI: 10.1049/iet-esi.2019.0014
|View full text |Cite
|
Sign up to set email alerts
|

Microgrids interconnection to upstream AC grid using a dual‐function fault current limiter and power flow controller: principle and test results

Abstract: This study presents a novel magnetic-based solid-state dual-function fault current limiter and power flow controller (FLPFC) that offers a promising application for safe and controllable interconnection of microgrids to upstream AC grids. The proposed structure includes series reactors and power electronic switches that protects microgrid from upstream AC grid shortcircuit fault and it controls the power flow between microgrid and upstream grid. Performance of the proposed FLPFC is analysed and simulated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…This resulted in the conception of microgrids, in which DGs can feed the distribution network with or without a power grid link [5,6]. Due to the multiple orientations of electric current in microgrids, protection schemes are based on DOCRs [7,8]. The DOCR setting parameters (DSPs) contain the current setting parameter (CSP) and the time setting multiplier parameter (TSMP).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in the conception of microgrids, in which DGs can feed the distribution network with or without a power grid link [5,6]. Due to the multiple orientations of electric current in microgrids, protection schemes are based on DOCRs [7,8]. The DOCR setting parameters (DSPs) contain the current setting parameter (CSP) and the time setting multiplier parameter (TSMP).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that using resistive-type SFCL limits the fault current as well as enhancing the transient stability in islanding mode. In [10], an inductive-type SFCL was used for interconnection between the AC-type MG to the main grid to control the short-circuit current and power flow. In [11], an inductive-type SFCL was used for the integration of the downstream wind-based DG to the main AC grid.…”
Section: Introductionmentioning
confidence: 99%
“…Since the capacity of RSC is 25–30% of the DFIG power rated, it cannot produce enough rotor voltage to counteract the stator voltage drop during severe voltage sag and needs the hardware protection scheme to cope with this problem [11 ]. In literature, several hardware schemes have been proposed and documented to meet the FRT requirement of the DFIG, which can be classified as (i) parallel reactive power compensation controllers include static synchronous compensator and static var compensator [12 ], (ii) dynamic voltage restorer [13 ], (iii) unified inter‐phase power controller [14, 15 ], (iv) series dynamic resistor [16, 17 ], (v) energy storage system [18 ], (vi) fault current limiters (FCLs) [19–41 ]. FCLs have been recognised as an attractive protection device in power system, which not only limits the magnitude of fault current [19–25 ], but also improves the power quality [26–28 ], the transient recovery voltage of circuit breaker [29, 30 ], and the system stability [31 ].…”
Section: Introductionmentioning
confidence: 99%
“…FCLs have been recognised as an attractive protection device in power system, which not only limits the magnitude of fault current [19–25 ], but also improves the power quality [26–28 ], the transient recovery voltage of circuit breaker [29, 30 ], and the system stability [31 ]. In [32–34 ], FCL has been introduced as a promising protection device for integration the downstream microgrids to the main AC grid. Recently, the application of FCLs is receiving more attention to cope with the FRT performance and fault current increment problems in WFs [35–41 ].…”
Section: Introductionmentioning
confidence: 99%